PELAKSANAAN KOMPETENSI PEDAGOGIK GURU SOSIOLOGI DALAM PROSES PEMBELAJARAN DI SMA NEGERI 1 SUNGAI RAYA - Sary, Hilda Aprilia; Budjang, Gusti; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis thesis is entitled ?The Implementation of Pedagogic Competence of Sociology Teachers in Learning Processes at SMAN 1 Sungai Raya?. The common problem is How the Implementation of Pedagogic Competence in Sociology Teachers in the Learning Processes at SMAN 1 Sungai Raya. The problems in this study are: 1) Knowing the characteristics of learners 2) Mastering of learning theory and the principles of learning sociology 3) Developing curriculum 4) Learning activities 5) Developing students potential 6) Communicating with students 7) Assessment and evaluation. The techniques which are used to collecting data are observation, interview and documentation. Then, the data collection tools in the form of observation and documentation guidelines. The results of this study indicated that: 1) Sociology teachers know the characteristics of students. 2) Sociology teachers master the learning theory and the principles of learning sociology 3) In developing the curriculum, sociology teachers still do not master. 4) The learning activities do in active activities; it can be seen from the teachers pay attention the students well. 5) Sociology teachers look active in developing students learning. 6) It has a good communication between the students and their teachers. 7) Sociology teachers always make an assessments and evaluations in learning. Keywords : Pedagogic Competence, Teachers, Sociology